PERSEPSI TENTANG STUNTING PADA REMAJA PUTRI DI KABUPATEN GIANYAR BALI - Sisilia Natanael; Ni Kadek Aprilia Putri; Kadek Tresna Adhi (Persagi, 2022)
ABSTRACT Stunting is a public health problem that reflects the condition of failure to thrive in children under five, resulting from chronic malnutrition in which the child's height does not match his age. The nutrition improvement movement of 8,000 first days of life is an effort to prevent stunting from pregnancy to adolescence. So it is necessary to know about the adolescent's perception regarding this stunting problem so that adolescents can have a crucial role in giving birth to a stunting-free generation in the future. The objective is to know the extent of the perception of stunting nutrition problems in adolescent girls at the stunting locus area in Gianyar Regency, Bali Province. This research is descriptive quantitative research with a cross-sectional study design. The sample of this study (411 respondents) was female high school students in Gianyar Regency and was selected using a non-probability sampling technique. Data on sociodemographic characteristics, sources of information related to nutritional problems, and perceptions related to stunting were collected using a google form questionnaire. Data analysis descriptively. The results showed that most (86.6%) respondents did not know that stunting was a nutritional problem for adolescents, and 50.4 percent of respondents had negative perceptions about stunting, especially in aspects of stunting prevention. These results indicate the importance of providing stunting prevention education models for young women, especially those that emphasize perceived seriousness and perceived benefits that awareness obtained to prevent stunting early. ABSTRAK Stunting merupakan masalah kesehatan masyarakat yang mencerminkan kondisi gagal tumbuh pada anak balita akibat dari kekurangan gizi kronis, sehingga tinggi badan anak tidak sesuai dengan umurnya. Gerakan perbaikan gizi 8.000 Hari Pertama Kehidupan (HPK) merupakan upaya pencegahan terjadinya stunting dari masa kehamilan hingga anak usia remaja. Maka perlu diketahui persepsi remaja terkait permasalahan stunting ini sehingga remaja dapat memiliki peran penting dalam melahirkan generasi bebas stunting di masa depan. Penelitian ini dilakukan bertujuan untuk mengetahui sejauhmana gambaran persepsi mengenai masalah gizi stunting pada remaja putri pada daerah lokus stunting di Kabupaten Gianyar, Provinsi Bali. Penelitian ini merupakan penelitian kuantitatif deskriptif dengan rancangan cross sectional study. Sampel dari penelitian ini adalah pelajar putri SMA di Kabupaten Gianyar sebanyak 411 responden yang dipilih menggunakan teknik non probability sampling. Data karakteristik sosiodemografi, sumber informasi terkait permasalahan gizi, dan persepsi terkait stunting diperoleh dengan menggunakan kuesioner google form. Analisis data dilakukan secara deskriptif. Hasil penelitian menunjukkan sebagian besar (86,6%) responden tidak tahu stunting merupakan masalah gizi remaja, serta sebesar 50,4 persen responden memiliki persepsi negatif tentang stunting terutama pada aspek pencegahan stunting. Hasil ini menunjukkan pentingnya pemberian model edukasi pencegahan stunting pada remaja putri terutama yang menekankan pada aspek persepsi keseriusan dan persepsi manfaat sehingga dapat diperoleh kesadaran untuk mencegah stunting lebih dini. [Penel Gizi Makan 2022, 45(1):1-10]